Evaluating the effect of entrepreneurial programs elements on students: A scale development - Elda Barron; Linda Elizabeth Ruiz (BAR: Brazilian Administration Review, 2021)
Entrepreneurship education is an approach that universities employ to attempt to produce more ventures. Currently, entrepreneurship education programs do not capture the perceived progress of their students because they lack such a method. In this study, we develop an instrument that measures students’ perceptions. We perform exploratory and confirmatory factor analyses based on the responses of 304 college students to identify the main factors that students consider in an entrepreneurship education program. The results show a measurement scale constituted by the following dimensions: learning, resources, instructor role, and a new dimension called the meaning of life. This new construct reflects the importance of factors beyond education or university resources and highlights individual perceptions. This study contributes to our understanding of the value that entrepreneurship education programs offer to their participants and provides insights into future adjustments to these programs.